2015
DOI: 10.1002/brb3.358
|View full text |Cite
|
Sign up to set email alerts
|

Altered resting perfusion and functional connectivity of default mode network in youth with autism spectrum disorder

Abstract: BackgroundNeuroimaging studies can shed light on the neurobiological underpinnings of autism spectrum disorders (ASD). Studies of the resting brain have shown both altered baseline metabolism from PET/SPECT and altered functional connectivity (FC) of intrinsic brain networks based on resting-state fMRI. To date, however, no study has investigated these two physiological parameters of resting brain function jointly, or explored the relationship between these measures and ASD symptom severity.MethodsHere, we use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
89
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(95 citation statements)
references
References 92 publications
(209 reference statements)
4
89
0
2
Order By: Relevance
“…Cerebral hypoperfusion has been demonstrated in ASD as compared to healthy controls in many parts of the brain, typically using positron emission tomography (PET) or single-photon emission computed tomography (SPECT) (Boddaert and Zilbovicius 2002, Galuska et al 2002, Sasaki 2015, Zilbovicius et al 1995, 2000. Further scanning methods such as fMRI were also adopted in ASD neuro-imaging with encouraging results (Dichter 2012, Jann et al 2015, Philip et al 2012. The hypoperfusion was detected on an individual basis in nearly 75% of the ASD children, with the current sensitivity of the imaging method (Zilbovicius et al 2000).…”
Section: Evidence For Cerebral Hypoperfusionmentioning
confidence: 99%
“…Cerebral hypoperfusion has been demonstrated in ASD as compared to healthy controls in many parts of the brain, typically using positron emission tomography (PET) or single-photon emission computed tomography (SPECT) (Boddaert and Zilbovicius 2002, Galuska et al 2002, Sasaki 2015, Zilbovicius et al 1995, 2000. Further scanning methods such as fMRI were also adopted in ASD neuro-imaging with encouraging results (Dichter 2012, Jann et al 2015, Philip et al 2012. The hypoperfusion was detected on an individual basis in nearly 75% of the ASD children, with the current sensitivity of the imaging method (Zilbovicius et al 2000).…”
Section: Evidence For Cerebral Hypoperfusionmentioning
confidence: 99%
“…The DE‐ASL acquisition had the same TE and the same number of time‐points of the cvBOLD acquisition for the ccBOLD part, but a lower temporal resolution. Nonetheless, it has been noted that the temporal resolution has only minor effects on FC estimation, while the total scan length is a critical factor affecting FC reliability (Birn et al, ; Jann et al, ; Smith et al, ). In particular, it has been suggested that longer duration acquisitions can maximize similarity of overall whole‐brain connectivity, with clear stability benefits for 10 min rather than 5 min scans (Gonzalez‐Castillo et al, ; Birn et al, ), and can yield more power for detecting smaller correlations while providing more precise estimates of the size of correlations [van Dijk et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…However, a short PLD would result in less T1 decay and thus higher SNR which is clearly advantageous for connectivity studies. Noteworthy, short PLDs with pCASL sequences (1,000–1,200 ms) have already been adopted by some researchers for concomitant connectivity analyses and CBF quantification [Cohen at al., 2016; Jann et al, ; Liang et al, ; Tak et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive symptoms produced by a failure within this network would involve decreased attention, mentalizing, decisionmaking, self-referential thought, and self-recognition. The default-mode network has been implicated in symptoms of a variety of neurocognitive disorders such as Alzheimer's disease (Greicius, Srivastava, Reiss, & Menon, 2004), Parkinson's disease (van Eimeren, Monchi, Ballanger, & Strafella, 2009), traumatic brain injury (Bonnelle et al, 2011), multiple sclerosis (Zhou et al, 2014), epilepsy (Haneef, Lenartowicz, Yeh, Engel, & Stern, 2014), autism (Jann et al, 2015). In ME, the relative interactions between nodes of the default-mode network could be examined using phase and coherence metrics within LORETA to explore temporal dynamics within a graph theoretical framework; the connectivity of edges between dysfunctional nodes identified as hyper/hypo connected according to EEG frequency band .…”
Section: Clinical Interpretation Of Dysregulated Network In Mementioning
confidence: 99%